Intention To Buy: What Drives Muslimah Consumers’ Purchase Intention Toward Fashion Lozy On Tiktok Shop - Kiki Melani; Erny Rachmawati; Herni Justiana Astuti; Purnadi Purnadi (Dinasti Review, 2026)
This study aims to analyze the influence of Social Media Marketing, Electronic Word of Mouth (eWOM), Celebrity Endorsement, and Brand Awareness on Purchase Intention toward Lozy products on TikTok Shop. This research employs a quantitative approach using a survey method. Data were collected through an online questionnaire distributed to 145 respondents residing in Purwokerto who actively use TikTok Shop. The data analysis techniques used include descriptive statistical analysis with the assistance of SPSS, as well as Partial Least Squares–Structural Equation Modeling (PLS-SEM) using SmartPLS. The results indicate that Social Media Marketing, Electronic Word of Mouth (eWOM), and Brand Awareness have a positive and significant effect on Purchase Intention, while Celebrity Endorsement does not have a effect on Purchase Intention. These findings suggest that effective digital marketing strategies, positive consumer reviews, and a high level of Brand Awareness play an important role in encouraging Muslimah consumers’ Purchase Intention toward Fashion products on the TikTok Shop platform.